Evaluation of Clinical and Laboratory Findings in Pediatric Cases with Diagnosis of Tuberculasis Peritonitis - Deveci, Ugur; Dogan, Yasar; Poyraz, Ahmet Kursat; Calik, Ilknur; Bakal, Unal; Kayaokay, Abdullah Murat; Hayirlidag, Mustafa (Bilimsel Tip Publishing House, 2026)
Objective: Tuberculasis peritonitis is a rare clinical entity in children. There are still difficulties in diagnosis. Therefore, pediatric cases diagnosed with tuberculasis peritonitis by laparoscopic biopsy were evaluated in this study. Material and Methods: Five pediatric cases diagnosed with tuberculasis peritonitis in our clinic between 2005 and 2024 were included in the study. Data regarding patients' demographic, clinical, laboratory findings, diagnostic tests, and post-discharge clinical follow-up were reviewed from hospital records. Results: Three of the patients were female and two were male. Mean age was 12 +/- 3 years. Median duration of complaints was 57 days (range: 15 and 90 days). No history of tuberculosis contact was detected in any case. The most common complaint was abdominal distension. Ascites was the most common finding on physical examination.Tuberculin skin test and interferon gamma release test were positive in only one case. The average adenosine deaminase level in the ascitic fluid was 65 UI/ dL. In this case, tuberculasis bacilli were isolated in ascitic fluid and sputum culture. The serum/ascites albumin gradient was below 1.1 g/dL in all cases. There was ascites on abdominal ultrasonography, and peritoneal thickening with ascites on abdominal computed tomography in all patients. Laparoscopic examination revealed peritoneal thickening and tuberous structures. Peritoneal biopsies revealed caseating chronic granulomatous inflammatory lesions consistent with a diagnosis of peritoneal tuberculosis. Median time to diagnosis was 14 days. Conclusion:Tuberculasis peritonitis should also be considered in the differential diagnosis in patients with ascites. Early diagnosis and treatment are possible thanks to laparoscopic biopsy together with laboratory and radiological examinations. Mortality and morbidity related to the disease can be prevented in this way.
Tüberküloz Peritonit Tanısı Alan Pediyatrik Olgularda Klinik ve Laboratuvar Bulgularının Değerlendirilmesi
Keywords: Tuberculasis peritonitis; child; laparoscopy; treatment